2021
DOI: 10.1016/j.jaad.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for cutaneous and pulmonary sarcoidosis: A case series

Abstract: Psoriasis is common, carries a substantial burden even when not extensive, and is associated with widespread treatment dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“… 13 Several other reports have documented successful treatment of sarcoidosis with JAK inhibitors. 14 16 Currently, a clinical trial of tofacitinib for cutaneous sarcoidosis and GA is underway (NCT03910543). We have found one case report of ulcerative NL responding to the JAK inhibitor, ruxolitinib, normally indicated for polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Several other reports have documented successful treatment of sarcoidosis with JAK inhibitors. 14 16 Currently, a clinical trial of tofacitinib for cutaneous sarcoidosis and GA is underway (NCT03910543). We have found one case report of ulcerative NL responding to the JAK inhibitor, ruxolitinib, normally indicated for polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%
“…9 While there is growing evidence for the efficacy of JAK inhibitors for treating inflammatory skin diseases such as atopic dermatitis, psoriasis, vitiligo, and alopecia, 9 the use of JAK inhibitors for granulomatous conditions has been relatively unexplored beyond case reports. [10][11][12][13][14][15][16][17] Increased knowledge of the role of JAK signalling in the inflammatory pathways involved has been reported. 18…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies used oral JAK inhibitors, including tofacitinib (JAK1/2/3), ruxolitinib (JAK1/2), and baricitinib (JAK1/2), and 2 studies used topical (compounded) 2% tofacitinib ointment. 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Key details of these reports are summarized in Table I . Two of the 3 ruxolitinib reports, which were among the earlier reports, were based on observations made in patients taking the medication for coexisting polycythemia vera, with incidental improvement in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding assessment of systemic disease, complete responses of internal organ sarcoidosis have been observed in 27% of patients treated with a JAK inhibitor and partial improvement occurred in the others. Kerkemeyer et al 8 showed, in a prospective series of 5 patients with pulmonary sarcoidosis treated with tofacitinib, that of 3 patients who completed the study, all had improvement in respiratory symptoms and were able to successfully taper their systemic glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…In a direct extension of these data, several case reports and 1 case series have shown improvement of primarily cutaneous sarcoidosis treated with the Janus protein tyrosine kinase (JAK) inhibitors [9][10][11][12][13][14]. However, pulmonary disease is the most common reason for treatment of sarcoidosis [15].…”
Section: Introductionmentioning
confidence: 99%